Original paperClinical practice trends in cryosurgery: a retrospective study of cutaneous lesions - Afsar, Fatma Sule; Erkan, Ceren Dagar; Karaca, Semsettin (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction : Cryosurgery is an alternative treatment for many benign, premalignant, and malignant lesions of the skin. Aim : To review the indications of cryosurgery for cutaneous lesions. Material and methods : The retrospective study was based on the assessment of medical records of 1031 dermatology patients who had cryosurgery. Results : One thousand two hundred and forty-four sessions of cryosurgery were applied to the total of 1031 patients. Of the 1031 patients, the most frequent indication for cryosurgery was common warts which were present in 535 (61.59%) patients, followed by anogenital warts in 119 (11.54%) patients, callosity in 81 (7.85%) patients, actinic keratosis in 77 (7.46%) patients, molluscum contagiosum in 35 (3.39%) patients, and other benign or malignant skin lesions. Conclusions : Cryosurgery is still a valuable treatment of choice in various benign, premalignant, and malignant skin diseases but seems to be underused for indications other than viral warts.